2020
DOI: 10.1186/s12889-020-09698-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gender, activity type, class location and class composition on physical activity levels experienced during physical education classes in British secondary schools: a pilot cross-sectional study

Abstract: Background Pupils in secondary schools do not meet the targets for physical activity levels during physical education (PE) sessions, and there is a lack of data on the vigorous physical activity domain (VPA) in PE known to be positively associated with cardio metabolic health While PE session intensity depends on a variety of factors, the large majority of studies investigating these factors have not taken into account the nested structure of this type of data set. Therefore, the aim of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 43 publications
0
10
1
2
Order By: Relevance
“…By giving the adolescents‘ self-organized PE the focus was to increase their intrinsic motivation in PE. Delextrat et al ( 2020 ) concluded that activity type could be associated with the intensity of PA in PE. By giving the adolescents‘ self-organized PE the purpose was to see if MVPA increased or went down in relation with the activity itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By giving the adolescents‘ self-organized PE the focus was to increase their intrinsic motivation in PE. Delextrat et al ( 2020 ) concluded that activity type could be associated with the intensity of PA in PE. By giving the adolescents‘ self-organized PE the purpose was to see if MVPA increased or went down in relation with the activity itself.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Kalajas-Tilga et al ( 2020 ) concluded that to enhance adolescents' daily MVPA, special focus should be put on increasing their intrinsic motivation toward physical education. Delextrat et al ( 2020 ) concluded that activity type could be associated with the intensity of PA in PE.…”
Section: Introductionmentioning
confidence: 99%
“… 47 48 The ‘Fit to Study’ pilot study (Delextrat, 2019) recorded an average figure of 30.7% MVPA when considering ‘effective’ PE time. 49 …”
Section: Discussionmentioning
confidence: 99%
“…47 48 The 'Fit to Study' pilot study (Delextrat, 2019) recorded an average figure of 30.7% MVPA when considering 'effective' PE time. 49 It has been suggested that a pursuit of PA alone may result in teachers prioritising fitness-based activities, at the expense of enjoyment and developing physically literacy. 50 However, our observations during the summer curriculum was that fitness-based activities were not prioritised, and that fielding and striking games lessons, one of the least active lesson types, were most commonly observed.…”
Section: Current Fitness Levels Of Young Uk Adolescentsmentioning
confidence: 99%
“…Lamentablemente las clases de educación física muestran una baja adherencia y tiempo de compromiso motor tanto en niños como adolescentes (Hollis et al, 2017;Reyes et al, 2020), lo que podría estar asociado a una baja motivación o baja percepción de autoeficacia (Arribas-Galarraga et al, 2020;Fraile et al, 2019;García et al, 2020;Wing et al, 2016). Dado el contexto actual, en el que cada vez existen menos oportunidades de acceder a un ambiente amigable que contribuya al desarrollo de habilidades motrices (Davids et al, 2016), es necesario que los profesores de educación física, diseñen sesiones que contribuyan a generar respuestas afectivas que motiven la participación y la percepción de autoeficacia con el fin de hacer de sus sesiones más efectivas (Baños et al, 2020;Delextrat et al, 2020;Lakicevic et al, 2020).…”
Section: Introductionunclassified